АҒЫН СУДАН БӨЛІНІП АЛЫНҒАН ДЕСТРУКТИВТІ БЕЛСЕНДІ ГЕТЕРОТРОФТЫ МИКРООРГАНИЗМДЕРДІ ИДЕНТИФИКАЦИЯЛАУ ЖƏНЕ ИММОБИЛИЗДЕУ (Experimental biology, 2017)
In this research work has been identified heterotrophic destructive bacteria of organic pollutants isolated from wastewater treatment facilities and studied their sorption activity on various types of sorbents.
Keywords: гетеротрофные бактерии